Micro foundations of price-setting behaviour: Evidence from Canadian firms - Daniel De Munnik; Kuan Xu (Bank of Canada, 2007)
How do firms adjust prices in the marketplace? Do they tend to adjust prices infrequently in response to changes in market conditions? If so, why? These remain key questions in macroeconomics, particularly for central banks that work to keep inflation low and stable. The authors use the Bank of Canada's 200203 price-setting survey data to investigate Canadian firms' price-setting behaviour; they also analyze the micro foundations for the firms' pricing behaviour using count data and probit models. The authors find that, all else being equal, firms tend to adjust prices more frequently if they are state-dependent price-setters, operate in the trade sector, or have large variable costs or more direct competitors. There are various sticky-price theories; in the Bank's price-setting survey, the senior management of firms were read a simple statement in non-technical language that paraphrased each sticky-price theory, and were then asked whether the statement applied to their firm. The most frequently recognized sticky-price theories are customer relations, cost-based pricing, and coordination failure. The authors' analysis indicates that if firms recognize coordination failure on price increases, sticky information, menu costs, factor stability, or customer relations as being important, they tend to adjust prices less frequently. The authors also find that the patterns discernible within firms' recognition of stickyprice theories are strongly associated with firms' micro foundations.
Keywords: D40; E30; L11; 330; Inflation and prices; Transmission of monetary policy; Betriebliche Preispolitik; Preisrigidität; Preisniveaustabilität; Transmissionsmechanismus; Ökonometrisches Modell; Kanada